Participação do peptídeo PACAP nas memórias de medo condicionado ao contexto e de reconhecimento social - Schmidt, Scheila Daiane (2015)
The PACAP neuropeptide (pituitary adenylate cyclase-activating polypeptide) has a wide spectrum of biological functions, such as neurotransmitter, neuromodulator, neuroprotective and neurotrophic factor. Furthermore, studies suggest that PACAP plays an important role in the modulation of social behavior, learning and memory, as well as the stimulation of nitric oxide (NO) production and modulation of the activity of the NMDA-type glutamatergic receptors. This study aimed to investigate, in the CA1 region of the dorsal hippocampus and the basolateral amygdala (BLA), the participation of PACAP in the contextual fear conditioning memory (CFC) and social recognition memory (SR). For this, adult male Wistar rats with cannulas implanted bilaterally in the CA1 region of the hippocampus or the BLA, were trained in contextual fear conditioning or social recognition tasks. It was observed that the PACAP antagonist (PACAP 6-38, 40 pg/side), when infused intra-CA1 or intra-BLA immediately after the training session of the CFC, impairs consolidation of memory. This effect was not observed when NMDA receptor agonist (D-serine, 50 μg/side) was infused concomitantly with PACAP 6-38. It was also found that when infused intra-CA1 immediately after the training session the extinction of the CFC, the PACAP 6-38 impairs memory of extinction, however, this effect was not observed in BLA or when the PACAP 6-38 was infused intra-CA1 concomitantly with D-serine. Further, it was found that when infused intra-CA1 or intra-BLA immediately after the social recognition task, PACAP 6-38 impairs consolidation of memory and this effect was not observed when nitrous oxide donor (SNAP; 5 μg/side) was infused concomitantly with PACAP 6-38. The results obtained in this study suggest that PACAP participates in the consolidation and extinction of CFC memory, and that this effect seems to occur through NMDA receptors. Furthermore, the results also indicate that PACAP participates in the consolidation of the social recognition memory, and that this effect seems to occur through the action of nitric oxide